2014
DOI: 10.1002/pen.23944
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of segmented poly(ether ester amide)s from diglycol, adipic acid, and a nylon‐6 oligomer

Abstract: This article presents a convenient method for synthesizing segmented poly(ether ester amide)s (PEEAs) by polycondensation and chain extension. A nylon‐6 oligomer prepared from ε‐caprolactam and ethanolamine through ring‐opening polymerization was polymerized with adipic acid and diglycol to prepare PEEA prepolymers (PrePEEAs) with ether linkages and amide contents ranging from 20 to 60 mol%. Chain extension of the PrePEEAs was conducted at 200°C using 2,2′‐(1,4‐phenylene)‐bis(2‐oxazoline) and carbonyl biscapro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…As for the hard segments, most of them have strong polar groups, such as urethanes, ureas, imides and esters 28 . In recent years, there has been an increasing interest in thermoplastic elastomers prepared from polyamide (TPAEs), due to their strong hydrogen bonding and intermolecular forces which could improve the thermal performance, chemical resistance, abrasive resistance, etc 29, 30 . A considerable amount of literature has been published on TPAEs.…”
Section: Introductionmentioning
confidence: 99%
“…As for the hard segments, most of them have strong polar groups, such as urethanes, ureas, imides and esters 28 . In recent years, there has been an increasing interest in thermoplastic elastomers prepared from polyamide (TPAEs), due to their strong hydrogen bonding and intermolecular forces which could improve the thermal performance, chemical resistance, abrasive resistance, etc 29, 30 . A considerable amount of literature has been published on TPAEs.…”
Section: Introductionmentioning
confidence: 99%
“…Theu niform distribution of C, O, N, and Fe elements in the Pep-APCDs@Feindicates the successful chelation of Fe ions, while not influencing the morphology of nanoassamblies (Figure 1b).The conjugation of AEAA on PEG-CDs (PCDs) was confirmed by the appearance of astretching vibration at 1618 cm À1 (C=Oofamide bond) before and after the surface modification in the Fourier-transform infrared (FT-IR) spectra ( Figure 1c). [13] Theformation of Pep-APCDs was accompanied with the variation in the characteristic peak at 1710 cm À1 (C=Oo fC OOH in Asp-Ala-Thr-Gly-Pro-Ala and at 1531 cm À1 (C-N of amide bonds). [14] Furthermore,t he molecular weights (MWs) of nanoassemblies was determined by gel permeation chromatography (GPC) and the values were 44.4 (CDs), 55.7 (PCDs), 61.2 (APCDs), 1114.0 (Pep-APCDs), and 1137.0 (Pep-APCDs@Fe/DOX-LOS) kDa ( Figure S2a-e), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, one problem with the PAs is the interchain forces that have negative effects on processability for high melting temperature. Thus, poly­(ester amide) (PETA), containing ester groups and amide groups, has gained attraction as a class of promising materials. , Many research groups reported the PETA crystallization, thermal and mechanical properties and the potential applications as biodegradable materials, biomedical materials, , and so forth. As one of the pioneers in the study of PETA, Gaymans and his colleagues have made a lot of basic research studies, providing a theoretical basis for our work .…”
Section: Introductionmentioning
confidence: 99%